My Ocean is Blue - Lebeuf, Darren; Barron, Ashley (Toronto, ON : Kids Can Press, 2020)
"A girl with a disability explores every facet of the ocean during a day at the beach ... A keen observer, she sees the ocean as both 'big' and 'small' and both 'sparkly' and 'dull.' It's also 'dotted and spiraled and wavy and straight.' Her ocean is full of sounds--it 'splashes and crashes' and 'laughs and hums.' But, at times, it's silent. She is inspired to examine and celebrate every part of her ocean and doesn't let anything hold her back"--
Keywords: Sea stories; Children and the sea -- Juvenile fiction; Children with disabilities -- Juvenile fiction; Ocean -- Fiction; People with disabilities -- Fiction